REFORMING LEGAL FRAMEWORKS FOR SCIENCE AND TECHNOLOGY EDUCATION IN NIGERIA: A PATHWAY TO INNOVATION IN TIMES OF NATIONAL CRISIS (UNIZIK Journal of STM Education, 2025)
The advancement of science and technology education is vital to Nigeria’s sustainable development and global competitiveness. However, persistent insecurity and economic crises have disrupted science teaching, exposed institutional weaknesses, and revealed the inadequacy of existing legal frameworks to support a resilient education system. The central problem this research addresses is the insufficiency of Nigeria’s current legal and policy structures to effectively safeguard and promote science and technology education, particularly in crisis-prone and underserved regions. This raises key research questions: To what extent do Nigeria’s legal instruments provide enforceable and adaptable support for science education? What legal reforms are necessary to make the system inclusive, resilient, and future-proof? The purpose of this study is to critically evaluate the legal and policy environment governing science and technology education in Nigeria, identify systemic gaps, and propose reformative measures aligned with international best practices. Drawing on a rights-based approach to education and the innovation systems theory, this paper employs qualitative legal analysis to review key statutes, including the Constitution, the National Policy on Education, the Universal Basic Education Act, and the National Science, Technology and Innovation Policy. Comparative models from Kenya, India, and South Africa are also examined to derive bestpractice insights. The findings reveal that although Nigerian laws acknowledge the importance of science education, they lack comprehensive, enforceable, and context-sensitive provisions necessary for effective implementation. The results show that the absence of digital infrastructure mandates, legal protections for virtual learning, and institutional coordination mechanisms undermines the delivery of science education, especially during national emergencies. The study recommends the enactment of a Science and Technology Education Reform Act, the inclusion of mandatory digital infrastructure provisions in relevant laws, and the development of legal protections for e-learning platforms to safeguard educational continuity. It further advocates for integrating adaptive learning frameworks and strengthening inter-agency collaboration.
Keywords: Education Reform, Legal Framework, Nigeria, Science and Technology Education